PERBANDINGAN KEJADIAN KONTAMINASI TELUR CACING SOIL TRANSMITTED HELMINTHES PADA SAWI (BRASSICA JUNCEA L) YANG DIJUAL DI PASAR MODERN DAN PASAR TRADISIONAL DI KOTA MEDAN - AMELIA AYUNI PUTRI; NELLI MURLINA (LP2MTBM MAKARIOZ, 2023)
Soil Transmitted Helminthes (STH) infection is an infection that has a fairly high incidence in the world. It is estimated that 60% of the world's population is infected with STH which plays an important role in causing death. The high infection rate is related to public hygiene, especially in consuming food, especially for food that is often eaten raw with less clean washing and the factor of using feces as organic fertilizer to make plants fertile. This study was conducted to compare the incidence of STH worm egg contamination in mustard greens (Brassica juncea L) sold in modern and traditional markets in Medan City. The research design used is analytic with a cross-sectional study. The sample used in this study amounted to 70 samples. Each sample of mustard greens was taken as many as 35 samples from modern markets and 35 samples from traditional markets in 21 sub-districts in Medan City. Then the samples were examined at the parasitology laboratory of the Muhammadiyah University of North Sumatra using the sedimentation method and eosin staining. From 70 samples, 24 samples of mustard greens from traditional markets were positive for STH contamination (68,57%) while 10 samples of mustard greens from modern markets were positive for STH contamination (28,57%). Based on the results of this study, it can be concluded that there is a significant difference in STH contamination in mustard greens sold in modern markets and traditional markets in Medan City as evidenced by the p- value obtained, which is 0.001 (p<0.05).